Intuitionistic Fuzzy Semi Î´-Preopen Sets and Intuitionistic Fuzzy Semi Î´-Precontinuity - Thakur, Samajh Singh; Rathor, Chandra Prakash; Bajpai, Jyoti Pandey (Journal of the Indonesian Mathematical Society, 2021)
The purpose of this paper is to introduce the concepts of fuzzy semi Î´-preopen sets and fuzzy semi Î´-precontinuous mappings in intuitionistic fuzzy topological spaces and obtain some of their properties and characterizations.